How to get published in the best management journals: Second edition - WRIGHT, Mike (Institutional Knowledge at Singapore Management University, 2020)
This expanded second edition of a classic career guide offers fascinating insight into the publishing environment for the management discipline, drawing on a wealth of knowledge and experiences from leading scholars and top-level journal editors. Responding to the continuing emphasis on publishing in the top journals, this revised, updated and extended guide offers invaluable tips and advice for anyone looking to publish their work in these publications.